Desempenho de criança de 7 a 10 anos em diferentes tarefas de controle postural - Kishi, Marcos Seizo (2005)
The aim of this study was to describe the effect of different tasks on the postural control of children aged between 7 and10 years old. Twenty-one children, divided into two age groups of 7-8 and 9-10 years old, participated in the study by performing 5 tests from the Balance Master System. The purpose of the first test was to verify the ratio of weight bearing to the levels of articular stress conferred by different degrees of knees flexion, and, according to ANOVA test, there were no differences either between the groups or among the conditions. Both the second and the fifth tests aimed to verify the influence of sensory cues on the postural control quantified by the sway speed; the former provided somatosensory and visual cues, and the latter, vestibular and visual cues. Kruskal-Wallis statistic test was applied to these two tests, and no differences were found between the groups. However, the groups showed distinct behaviors in relation to the conditions. The second test indicated that the alteration in somatosensory input resulted in maximal instability of the postural control, while the fifth one verified maximal instability when vestibular input was altered. The aim of the third test was to identify the response of the control motor components during the performance of tasks that involve intentional movement of the center of body mass toward the target. The group of 7-8-year-old children showed better performances in Endpoint Excursion (EPE) and Movement Velocity (MV), and it seems to be related to cognitive aspects of the task. The forth test aimed to relate the variables of gait to the maintenance of the stability following its achievement, and, although no differences were found between the groups, it was verified positive correlations between anteroposterior body sway and step width as well as progression velocity. Regarding the postural control, it is possible to conclude that the age influenced the variables EPE and MV, since the age group of 7-8 years old showed better performances. In addition, postural as well as motor control of the children was influenced by sensory cues of the tasks.